Patents and the financial performance of firms - An analysis based on stock market data - Peter Neuhäusler; Rainer Frietsch; Torben Schubert; Knut Blind (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2011)
The following article systematically analyzes the question of how the results of R&D and its protection - or so to say, the technology base of a firm - can influence its market value and profits. Based on theoretical arguments it is hypothesized that large and highly valuable patent portfolios of firms have significant effects on their competitiveness in the long run. For the empirical testing a panel dataset including 479 firms from 1990 to 2007 based on the DTI-Scoreboard is used, which contains data on R&D expenditures, market capitalization, turnover etc. and structural information like firm-size and industry sector. To this database the relevant information on patenting behavior and financial performance are added, so effects of firm characteristics can be calculated. To assess the value of a firm's patent portfolio, different value measures like the number of received patent citations, opposed patents, number of inventors etc. are being applied. The results suggest that at least at the firm level, especially forward citations and family size positively influence market value. Concerning the Return on Investment, especially oppositions and family size show positive effects. This leads to the conclusion that securing international markets has a positive effect on the value of the firm in the home market.
urn:nbn:de:0011-n-1582128
Keywords: 330